The screening of compounds regulating PD‐L1 transcriptional activity in a cell functional high‐throughput manner - Lanxin Zhang; Hexin Li; Jingchao Liu; Gaoyuan Sun; Xiaokun Tang; Siyuan Xu; Lili Zhang; Wei Zhang; Bin Ai (Cancer Medicine, 2023)
Abstract Immune checkpoints are protein molecules expressed on the immune cell membrane, which regulate the immune system to kill tumor cells. As an essential immune checkpoint, overexpressed PD‐1 on tumor cells could inhibit T‐cell activation after being bonded to PD‐1. Due to this inhibitory effect, T‐cell proliferation and cytokine secretion are suppressed, leading to immune escape of tumor cells. Here, we established a high‐throughput method based on cell function screening technology to screen drugs regulating PD‐L1 expression in tumor cells at the transcriptional level. After two screening rounds, 12 compounds that enhanced PD‐L1 transcription while seven weakened were sorted out among 1018 FDA‐approved drugs. Finally, a tumor cell line was used to verify the upregulation of endogenous PD‐L1 expression for a drug named “vorinostat,” a histone deacetylation inhibitor, after the two rounds of optional selection. Therefore, our research provides another perspective for using “vorinostat” in treating tumors and offers a convenient method to detect the transcriptional expression of other intracellular proteins besides PD‐L1.